2021
DOI: 10.1111/andr.12961
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis, erectile dysfunction, reproductive hormones, and semen quality: A systematic review

Abstract: Background There is increasing evidence that periodontitis may affect male sexual health (MSH) (erectile function, production of sex hormones, and semen quality). However, a limited number of clinical studies demonstrate the association between MSH and periodontitis. Objectives The aim of this study was to explore the relationship between periodontitis and MSF. Materials and methods A comprehensive systematic review of the published literature in MEDLINE, PubMed, Scopus, Cochrane, EMBASE, and Web of Science da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Another significant finding from this study was the lack of association between the sex of each subject and the distribution of Selenomonas within the study samples. Many other studies have found significant differences between males and females with respect to the development and progression of periodontal disease and the prevalence of specific periodontal pathogens [ 36 , 37 , 38 ]. The lack of sex-specific associations with this organism is consistent with other recent studies that have included both pediatric and adult patient populations, strongly suggesting that the traditional risk factors of sex and age may not be the most important factors to determine which patients harbor Selenomonas [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another significant finding from this study was the lack of association between the sex of each subject and the distribution of Selenomonas within the study samples. Many other studies have found significant differences between males and females with respect to the development and progression of periodontal disease and the prevalence of specific periodontal pathogens [ 36 , 37 , 38 ]. The lack of sex-specific associations with this organism is consistent with other recent studies that have included both pediatric and adult patient populations, strongly suggesting that the traditional risk factors of sex and age may not be the most important factors to determine which patients harbor Selenomonas [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated associations between periodontitis and conditions such as diabetes, cardiovascular diseases, and erectile dysfunction [21][22][23]. Among these, diabetes emerges as a high-risk factor for both hearing impairment and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…[121][122][123] TNF-α has been reported to play a key role in the induction of endothelial dysfunction. 124,125 Multiple studies have reported a reduction in TNF-α levels after successful periodontal treatment, and it is evident that significantly higher plasma levels of TNF-α were associated with moderate to severe ED owing to their known effects on the vasculature. 126,127 Management of oral biofilm and periodontal health can therefore have positive implications in the management of ED.…”
Section: Erectile Dysfunction (Ed)mentioning
confidence: 99%